G07 The Impact of START: Driving the Learning. (4th June 2013) - Davies-Muir, A; Newell, S; Muir, G; Simpson, M
Abstract : Aims: START is designed to assess the readiness for consultant practise of senior trainees. Consequential validity is reported by examining adjustment in trainees' behaviour and practise following feedback from START. These data will inform level 3 training needs and development of the new START assessment. Methods: Questionnaires were distributed via SurveyMonkey to the 59 trainees being assessed and the 37 assessors, with a respective response rate of 74.6% and 73%. A semi-structured approach collected data using Likert scales, combined with open ended questions. Analysis addressed both quality and organisational issues. Summarised responses to the Likert scales are reported. Open ended questions were explored using thematic content analysis and main areas for development visualised with word clouds. Follow up data will be analysed and reported using a longitudinal approach to examine the impact of reflective changes to practise following the feedback from the assessment. Results: 74.4% of trainees and 100% of assessors recognised START as a good assessment of skills that are not assessed elsewhere such as safe prescribing, critical appraisal and management of complexity. 64.3% of trainees and 100% of assessors noted that START was a good assessment of 'readiness' for consultant practise. START assesses a range of skills requiring appropriate leadership and understanding team dynamics. Assessors identified leadership, prioritisation, multidisciplinary working and decision making as being the most predominant areas for development when considering all the trainees. This differed slightly from areas identified for development within the sub-specialties which included knowledge. Assessors believe START will impact on trainees' learning and practise behaviour, emphasising importance of reflection and identified action on the feedback. They consider it fit for purpose in helping with the transition of becoming a consultant and focussing the trainees on areas needed for further development. This information prompts trainees to actively seek opportunities in identified domains to improve and gain further experience. Future longitudinal follow-up evaluation and analysis of the impact of START will be undertaken. Conclusion: START provides new and useful feedback on trainee's behaviour and practise and a focused learning plan in readiness for consultant practise. Initial findings indicate the importance of attitude and 'buy in' amongst trainees.